a) 3x-3y+x²-xy=3(x-y)+x(x-y)=(x-y)(3+x)
b)3ax-a+6x-2=a(3x-1)+2(3x-1)=(3x-1(a+2)
c) 2a²x+ax²+2ax+x²=ax(2a+x)+x(2a+x)=x(2a+x)(a+1)
d)5ax²+4ax+15x+12=ax(5x+4)+3(5x+4)=(5x+4)(ax+3)
e) 2x+3y+2x²+3xy+4xy²+6y³= (2x+3y)+x(2x+3y)+2y²(2x+3y)=
=(2x+3y)(1+x+2y²)
f)(x+1)²-9=(x+1-3)(x+1+3)=(x-2)(x+4)
g)16-(2x-3)²=(4-2x+3)(4+2x-3)=(7-2x)(1+2x)
h) x³+x²y-4x-4y=x²(x+y)-4(x+y)=4(x-y)(x²-4)=4(x-y)(x-2)(x+2)
i)6x²-10x+4=2(3x²-5x+2)=2(3x²-2x-3x+2)=2[x(3x-2)-(3x-2)]=2(3x-2)(x-1)
j)2ay+3ax-4y-6x=a(2y+3x)-2(2y+3x)=(2y+3x)(a-2)
k)20x²-12xy√5+9y²=(2x√5-3y)²
l)x-2y+4x²-8xy+3x²y-6xy²=(x-2y)+4x(x-2y)+3xy(x-2y)=(x-2y)(1+4x+3xy)